Checklist of the Tribe Spilomelini (Lepidoptera: Crambidae: Pyraustinae) in Thailand - Sunadda Chaovalit; Nantasak Pinkaew (Agriculture and Natural Resources, 2020)
In total, 100 species in 40 genera of the tribe Spilomelini were confirmed to occur in Thailand based on the specimens preserved in Thailand and Japan. Of these, 47 species were new records for Thailand. Conogethes tenuialata Chaovalit and Yoshiyasu, 2019 was the latest new recorded species from Thailand. This information will contribute to an ongoing program to develop a pest database and subsequently to a facilitate pest management scheme in Thailand.